2021
DOI: 10.1016/j.asmr.2020.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The Fifty Most-Cited Articles Regarding SLAP Lesions

Abstract: Purpose To identify and evaluate the top 50 most-cited articles pertaining to SLAP tears. Methods The ISI Web of Knowledge database was used to conduct a query for articles pertaining to SLAP tears. Our query was conducted in April 2020 with multiple Boolean operative combinations performed by 2 independent reviewers. Articles on the final list were further reviewed to extract the following data: manuscript title, first author, total citation count, year of publication,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This is a far greater proportion of high LOE studies than identified for other orthopedic fields of study. 13 , 15 This serves as relative affirmation that these articles in patellar tendon injury research are not just influential but also of high-quality evidence. Of the 10 studies with LOE I, 8 of them focused on nonoperative management and covered therapies such as platelet-rich plasma and corticosteroid injections, once again demonstrating the importance clinicians and researchers in this field have placed on evaluating nonoperative therapies.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This is a far greater proportion of high LOE studies than identified for other orthopedic fields of study. 13 , 15 This serves as relative affirmation that these articles in patellar tendon injury research are not just influential but also of high-quality evidence. Of the 10 studies with LOE I, 8 of them focused on nonoperative management and covered therapies such as platelet-rich plasma and corticosteroid injections, once again demonstrating the importance clinicians and researchers in this field have placed on evaluating nonoperative therapies.…”
Section: Discussionmentioning
confidence: 88%
“…Previous bibliometric analyses have demonstrated in many cases that the most-cited articles are not always of the LOE, and have identified specific areas where further impactful research would benefit different fields of medicine. 13 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous bibliometric analyses demonstrating that in many cases the most cited articles are not always of the highest LOE. 1 , 2 , 17 This finding reveals the opportunity and relative need for prospective research to improve the quality of evidence with which football team physicians make evidence-based decisions. We acknowledge, however, that performing randomized and prospective research can be difficult in this population, which often involves teams of ≥50 players with varying schedules outside their sports participation.…”
Section: Discussionmentioning
confidence: 92%
“…These analyses have been frequently utilized in recent years to allow identification and evaluation of the most influential articles within a field of study, based on total citations and citation density (ie, citations per year since publication). 1 , 2 , 8 , 17 , 21 , 57 , 69 Among the many benefits of such analyses is the ability for educators to facilitate creation of efficient reading programs for residents and fellows to cover the most influential articles in a field of study. Second, these data are useful for researchers to ensure that they are abreast of the most influential articles and to identify key evidence before designing their research questions.…”
mentioning
confidence: 99%